ANALISIS SIKLUS PEMBELIAN (STUDI KASUS : PT.BERKAT UNGGULTAMA INDONESIA) - Dinda Adani Sarwanto Putri; Akie Rusaktiva Rustam (Jurnal Ilmiah Mahasiswa FEB, 2012)
Accounting information system role in the company is provide accurate and reliable information  to assist management in decision making and as a survelliance and controlling of the company’s activity. This research aim to understanding the system  in purchasing cycle at PT.Berkat Unggultama Indonesia, analyze whether there is weakness of the system,  and create a solution for problem that exist by designed a manual system. This is a descriptive qualitative research. Data used in this research obtained through interview, collecting document, and observation. Based on this research, the problem in purchasing cycle at PT.Berkat Unggultama Indonesia is the lack of an adequate organizational struture, and lack of internal control. These weakness needs to be fixed  by proposed new organizational structure, management’s policy, accounting policy in company, and new standart operating procedures. Keywords : Accounting Information System, Purchasing Cycle, Internal Control